Incidental brain MRI findings in an autism twin study. Issue 1 (22nd November 2016) - Monterrey, Julio C.; Philips, Jennifer; Cleveland, Sue; Tanaka, Serena; Barnes, Patrick; Hallmayer, Joachim F.; Reiss, Alan L.; Lazzeroni, Laura C.; Hardan, Antonio Y.
Abstract : Brain magnetic resonance imaging (MRI) studies suggest the prevalence of asymptomatic "incidental" findings (IF) in autism spectrum disorder (ASD) is similar to that of neurotypically developing (NT) controls. However, given the causes of IF may include both genetic and environmental factors, a twin study would facilitate comparing brain IF between ASD and NT subjects. MRI scans were examined to assess the prevalence of brain IF in twin "case pairs" (at least one twin with diagnosis of ASD) and twin "control pairs" (NT). Fifty case pairs and thirty‐two control pairs were analyzed. IF were found in 68% of subjects with ASD, 71% of unaffected ASD siblings, and in 58% of control subjects ( P = 0.4). IF requiring clinical follow‐up occurred more frequently in subjects with ASD compared to NT controls (17% vs. 5%, respectively; P = 0.02). The concordance rate of IF in twins was 83%. A mixed effects model found younger age, male sex, and "family environment" to be significantly associated with IF. There was no difference in the prevalence rate of IF between ASD subjects and NT controls. More IF required clinical follow‐up in ASD subjects compared to NT controls. The prevalence rate of IF observed in this twin study was higher than rates previously reported in singleton studies. Our results suggest the shared environment of twins – perhaps in utero – increases the risk of brain IF. Brain MRI in the initial work‐up of ASD may be indicated in twins, especially in males. Autism Res 2017, 10: 113–120 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.